Single-step self-punching lockbolt process and equipment development for pre-hole-free joining of aluminum sheets using a dual-die system - Böhm, Yannic; Kappe, Fabian; Han, Daxin; Nordmann, Elmar; Yang, Keke; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)

Deformationsarme Fügeverbindungen mittels prozessoptimiertem Schneidclinchen - Han, Daxin
Lightweight materials such as aluminium and ultra-high-strength steel are increasingly being used in modern material mixed design in car body construction. As a fixing method for hybrid joining with structural adhesive, clinching has the advantage over other mechanical joining technologies that different materials can be joined without an auxiliary joining part and pre-hole. Due to the large degree of deformation in the joining partners, strong in-plane and out-of-plane material flows occur during the setting process, which can lead to plastic deformation. The aim of this work is the further development of shear-clinching for low-deformation of aluminium-steel joints. To gain a basic understanding of the joint deformation, the deformation of the joint partners during the setting process is identified step by step. Based on the knowledge gained, the deformation-related influencing factors are investigated experimentally. Thus, optimisation approaches as well as suggested handling methods for the production of a low-deformation shear-clinching joint are derived. For the realisation of the common narrow flange, which is to be characterised as deformation-sensitive due to a small edge distance, a numerically supported tool modification is carried out and subsequently experimentally validated.

Qualifizierung mechanischer Fügeverfahren für Batteriekästen - Han, Daxin; Meschut, Gerson

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Mechanisches Fügen von FKV-FKV-Verbindungen - Han, Daxin; Meschut, Gerson
Within the scope of the research project, four new mechanical joining processes for the singlestage, pre-hole-free joining of FRP-FRP joints were further developed. For this purpose, the joining processes under consideration were first implemented on existing equipment at the research institute. Based on the successful adaptation of the joining processes, characteristics of the joints were documented by means of micrographs and observation of external characteristics, on the basis of which measures for process modification were derived. The process modifications were carried out on a process-specific basis for a selected GFRPGFRP joint. The aim was to improve the joint quality, in particular with regard to the reduction of laminate damage, by means of targeted element and tool development in addition to the increase in process stability. Based on these results, a realistic suitability evaluation of the joining methods was carried out with regard to process and manufacturing flexibility. As a result, two self-piercing riveting processes, which showed the greatest suitability potential, were examined in more detail to analyse the application limits. In the process, the joints were sampled on further material combinations with varied fibre and matrix systems. In addition, joints with adhesive were investigated, in which the influence of the adhesive viscosity on the joint properties was analysed. The joint properties of the new joining method were then comprehensively determined by tensile tests under quasi-static, cyclic loads. Finally, the behaviour of the optimised joints under corrosive load was characterised in the salt spray test. Through the targeted process modifications in this project, the FRP-FRP joints can be joined with less damage, enabling improved joint quality in the FRP-based components.

A method for three-dimensional modelling of the shear-clinching process - Han, Daxin; Yang, Chen; Meschut, Gerson (ESAFORM 2021)
Three-dimensional modelling enables to determine the in-plane material flow in asymmetrical situation. Thus, the distortion of the sheets to be joined can be characterized more exactly. This study shows a method for building up a three-dimensional shear-clinching framework without damage criteria. In fact, the die-sided sheet in shear-clinching was designed as a pre-punched sheet and slugs. The material separation in the die-sided joining partner, which in two-dimensional simulation is often described by macro- and micromechanical fracture criteria, was realised in this study based on a defined contact condition. By means of a shear-cutting simulation, a correlation between the break angle and the separation stress was determined, which was used as a separation criterion in the shear-clinching simulation. The separation line was confirmed using post-particles. To validate this model, the results of the simulation using a quadratic single-point specimen were compared to the experiments with respect to the distortion of the joining partner. In general, the built three-dimensional framework provides for further tool developments with regard to the reduction of distortion in shear-clinching.

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Untersuchung der Werkzeugbeanspruchung und des Verschleißes beim Schneidclinchen

Geometric and corrosive influences on load-bearing capacity of multi-element shear-clinching specimen - Han, Daxin; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)

Investigation of the tool wear behaviour in shear-clinching processes during the running-in phase - Wiesenmayer, Sebastian; Han, Daxin; Meschut, Gerson; Merklein, Marion (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)

Fundamental mechanisms and their interactions in shear‐clinching technology and investigation of the process robustness - Wiesenmayer, S.; Han, Daxin; Müller, M.; Hörhold, R.; Meschut, Gerson; Merklein, M. (Materialwissenschaft und Werkstofftechnik)

Numerical Investigation of the Tool Load in Joining by Forming of Dissimilar Materials Using Shear-Clinching Technology - Wiesenmayer, Sebastian; Müller, Martin; Dornberger, Peter; Han, Daxin; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Modern developments in the automotive sector are motivated by the objective of lowering the emission of pollutants. In contrast, growing demands for safety and comfort lead to a potential increase of the weight of vehicles. Thus, the consequent use of lightweight design is indispensable. This includes the use of different materials for the construction of car bodies. Because of various material properties, joining of dissimilar materials is challenging and requires often the application of non-thermic processes like riveting or clinching. These processes are limited by the mechanical properties of the joining partners. Especially the increasing use of ultra-high strength alloys, like the hot stamped steel 22MnB5, makes the development of new joining technologies necessary. One of these innovative technologies is shear-clinching. By combining shear-cutting and clinching in one process, this technology produces durable and tight connections of dissimilar materials with high differences regarding strength and formability. In contrast to shear-cutting the die-sided material has no contact with the punch. Since the process of shear-clinching is a combination of cutting and joining using the same tool, the tool loads differ from common shear-cutting. Especially cutting hot stamped steels is a challenge due to their high ultimate strength which leads to high tool loads. Thus, the analysis of the load condition is essential for the dimensioning of durable and wear resistant tools. Hence, the scope of this paper is a numerical investigation of the tool loads during the indirect cutting process and the subsequent step of joining by forming during shear-clinching. Since an experimental investigation of the occurring tool loads in the closed process is not practicable, the finite element method has to be used. Therefore, a damage-based numerical model is set up to enable the coupled simulation of the combined cutting and joining process and the resulting tool loads. This allows the analysis of the loads during the whole process, identifying the influences of materials and sheet thicknesses.

Investigation of the influence of tool-sided parameters on deformation and occurring tool loads in shear-clinching processes - Han, Daxin; Hörhold, Réjane; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (Procedia Manufacturing)

Shear-Clinching of Multi-Element Specimens of Aluminium Alloy and Ultra-High-Strength Steel - Han, Daxin; Hörhold, Réjane; Müller, Martin; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (Key Engineering Materials)
The newly developed joining-by-forming technology “shear-clinching”, features a potentially single-stage process for joining UHSS without requiring any additional elements. Foundational studies have focused on the functionality of shear-clinching at a one-element sample. To ensure the safety of the industrial application of the shear-clinching technology, an investigation with component-like samples with several joints is required. This paper presents a detailed analysis of the material behaviour during the shear-clinching process with multi-element specimens to evaluate the influence of the neighbouring joints. In order to describe the influence of the neighbouring joints, the deformations resulting from the bending and material displacement are recorded without contact after the joining process: locally around the joining point and globally over the entire sample size. To minimize such bending effects, a tool-sided adaptation is provided. The results show the high potential of shear-clinching joining by UHSS and give further recommendations for future multi-material application.